The Role of Oxytocin in Cardiovascular Protection - Jankowski, Marek; Broderick, Tom L.; Gutkowska, Jolanta (Frontiers in Psychology, 2020)
The beneficial effects of oxytocin on infarct size and functional recovery of the ischemic reperfused heart are well documented. The mechanisms for this cardioprotection are not well defined. Evidence indicates that oxytocin treatment improves cardiac work, reduces apoptosis and inflammation and increases scar vascularization. Oxytocin-mediated cytoprotection involves the production of cGMP stimulated by local release of atrial natriuretic peptide and synthesis of nitric oxide. Treatment with oxytocin reduces the expression of pro-inflammatory cytokines and reduces immune cell infiltration. The beneficial actions of oxytocin may include the increase in glucose uptake by cardiomyocytes, reduction in cardiomyocyte hypertrophy, decrease in oxidative stress, and mitochondrial protection of several cell types. In cardiac and cellular models of ischemia and reperfusion, acute administration of oxytocin at the onset of reperfusion enhances cardiomyocyte viability and function by activating Pi3K and Akt phosphorylation and downstream cellular signaling. Reperfusion injury salvage kinase and signal transducer and activator of transcription proteins cardioprotective pathways are involved. Oxytocin is cardioprotective by reducing the inflammatory response and improving cardiovascular and metabolic function. Because of its pleiotropic nature, this peptide demonstrates a clear potential for the treatment of cardiovascular pathologies. In this review, we discuss the possible cellular mechanisms of action of oxytocin involved in cardioprotection.